THE EFFECT OF CUSTOMER REVIEWS AND PRODUCT QUALITY ON BUYING INTEREST THROUGH PRODUCT UNDERSTANDING (CASE STUDY: GLAD2GLOW) - Indah Lestari; Nurlaila; Kusmilawaty (RADJA PUBLIKA, 2025)
This study aims to determine the effect of customer reviews and product quality on purchasing interest through product understanding from Glad2Glow. The sampling technique uses non-probability sampling with a purposive sampling method with a sample size of 100 respondents. Using the Multiple Linear Regression method and using the SPSS22 application. This study uses a quantitative approach. The data source used in this study uses primary data obtained from distributing questionnaires to respondents. This study aims to analyze the effect of customer reviews and product quality on consumer purchasing interest with product understanding as an intervening variable in the Glad2Glow product. The results of the study indicate that customer reviews play an important role in increasing consumer understanding of a product. Clear, informative, and positive reviews help consumers understand the advantages, disadvantages, and overall experience of using the product, thus forming trust and encouraging purchasing interest. In addition, product quality has also been shown to have a positive and significant influence on purchasing interest.